Influence of water stress and pH in germination process of "algarobeira" seeds - Gualtieri de Andrade Perez, Sonia Cristina Juliano; de Moraes, José Antônio P.V (Pesquisa Agropecuaria Brasileira, 1991)
The aim of this work was to study the effects of water stress and pH on the germination of Prosopis juliflora seeds. They were put into sulfuric acid during 30 seconds before being placed in a growth chamber at 35°C. Drought was simulated by using mannitol, and a decrease in the rate and percent of germination was observed with the increase of water stress. The germination was strongly inhibited at -19,0 bar. The pH did not cause significant inhibition in the rate and percentage of germination over the wide range of 2 to 12. This fact indicated that this species is an amphitolerant one.